Modeling the personal adult learner: the concept of PLE re-interpreted. Issue 6 (17th August 2020) - Fiedler, Sebastian H. D.; Väljataga, Terje
ABSTRACT: This paper argues for conceptualizing the notion of personal learning environments in higher education from an explicit adult education perspective that emphasizes the realization, re-instrumentation, and integration of learning activity in the wider context of adult life. It discusses and re-interprets an existing proposal for modeling "the personal learner" on the basis of the Viable System Model in this context and provides an empirical illustration for the conceptual utility of such an approach for educational intervention work in higher education. The paper concludes that a careful redesign and reconfiguration of learning activity in formal educational settings is a necessary and important educational intervention goal in itself, allowing for expansive connections between specific forms of learning activity and the wider context of adult life. Such an approach treats participants as developing "adult learners" who gradually gain conscious control over their own modeling of learning activity, its flexible realization via personal learning projects, and their instrumentation via personal learning environments.